A Comparison of Academic Achievement and Well-Being of Students Studying in Mid and Full-Day Private Schools - Uzair ulhassan; Iram Parveen; Farhan Malik (NUML Journal of Critical Inquiry, 2022)
This study aims to compare the academic achievement and socio- emotional well-being of students studying in mid and full-day schools located in the district Sargodha, Punjab, Pakistan. Initially, the schools are carefully selected from the population. Then 163 students from mid-day schools and 219 students from full-day schools are randomly selected which made a sample of 382 students in total. To collect the data, we adapted the questionnaire comprising five factors based on the work of Schonert-Reichl, et al. (2012) concerning promoting children’s prosocial behaviors in schools. The results of our study show that though the academic achievement of full-day students is better, it is at the cost of their social and emotional well-being. The students of full-day schools exhibit problems of having less peer interaction, short-temperedness and emotional imbalance as compared to students at mid-day schools, though mid-day school students are also not completely free of such issues. However, the students from full-day schools show some positive attributes of developing more social skills related to volunteerism, kindness, and helping peers and other people in schools. The study thus suggests that students need to be engaged in schools for longer hours, so that they may develop autonomy and responsibility along with making their academic achievements better. However, schools may provide continuous counseling sessions to students for their better social and emotional well-being.